Perbandingan Metode Simple Additive Weighting dan Weighted Product Pada Keputusan Pemberian Bantuan (Desa Cisarua, Kabupaten Sukabumi) - Rizka Aulia Fazri (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Providing assistance is one of the programs carried out by the government through representatives of each region to help community’s economy, especially those related to the problems caused by Covid-19 pandemic. Ideally, the determination of the provision of assistance can be done quickly, objectively and on target. However, the decision-making process in Cisarua village, Sukabumi district is still done manually where there is no method used in that process leads decision makers to face problems in determining assistance recipients with the large number of people and multicriteria. Thus requiring a long time, leading to subjective judgements and providing assistance that is not on target. Simple Additive Weighting (SAW) and Weighted Product (WP) are multicriteria methods that can be applied in the decision-making process, both methods are compared to find out the best method in determining the appropriate and targeted assistance recipients. The research starts from the problem identification which includes data collection, analysis, and application of the multicriteria method to the interpretation of method comparison results. The SAW method is more appropriate to be applied in determining the provision of assistance in Cisarua village by producing a higher number of rankings and percentage value of suitability level than the WP.